Old Perineal Rupture - From Diagnosis to Reparation: Ruptur Perineum Lama: Diagnosis sampai Perbaikan - Budi I. Santoso; Nadir Chan; Leonardo Leonardo (Indonesian Journal of Obstetrics and Gynecology, 2019)
Abstract Objective: To describe and discuss the technique to diagnose, preparing the reparation and postoperative management in old perineal rupture case.Methods: A 28-year-old primipara woman was referred to YPK Mandiri Hospital after having incontinence to flatus, to urinate and passive soiling. Three months before admission, she had her first child through vaginal delivery.Discussion: She was diagnosed with a third-degree obstetric anal sphincter injury (OASIS). Rectal examination with digital palpation (pill-rolling motion) and ultrasound examination, revealed a distinct gap anteriorly (10 – 2 o'clock). End to end technique was preferred to repair the defect.Conclusion: A good understanding of perineal and anal sphincter anatomy is essential to diagnose OASIS. The aim of reconstructive surgery is to restore the continuity of both the external and internal anal sphincters. Ideally, the repair should be performed as soon as possible after the injury.Keywords:obstetric anal sphincter injuries, OASIS, third-degree tear, perineum, perineal trauma. Abstrak Tujuan:Untuk mendeskripsikan dan diskusi tentang tehnik dalam mendiagnosa, mempersiapkan operasi reparasi dan manajemen pasca operasi pada kasus rupture perineum lama.Metode:Sebuah laporan kasus yang diambil dari pasien perrempuan 28 tahun primipara yang dirujuk ke RS YPK Mandiri setelah mengeluhkan inkontinensia flatus, urin, dan keluarnya feses tanpa disadari. Tiga bulan sebelumnya, pasien melahirkan anak pertama melalui persalinan pervaginam.Diskusi: Diagnosa pasien adalah cedera sfingter ani obstetrik derajat tiga. Pemeriksaan rektal dengan palpasi digital (gerakan pill-rolling) dan pemeriksaan ultrasonografi, memperlihatkan adanya penipisan di daerah anterior (arah jam 10 – 2). Teknik end to end dipilih untuk memperbaiki defek.Kesimpulan:Pengetahuan yang baik mengenai anatomi perineum dan sfingter ani penting untuk mendiagnosis OASIS. Tujuan utama dari operasi rekonstruksi adalah untuk memperbaiki kontinuitas dari sfingter ani eksternal dan internal. Idealnya, reparasi dilakukan secepat mungkin setelah terjadinya cedera. Kata kunci: cedera sfingter ani obstetrik, OASIS, perineum, trauma perineum, robekan derajat tiga